2018
DOI: 10.21873/anticanres.12282
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Structure–Cytotoxicity Relationship of 2-Azolylchromones

Abstract: Chemical modification of the lead compound may be a potential choice for designing a new type of anticancer drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 7 publications
(9 reference statements)
0
17
0
Order By: Relevance
“…We investigated a total 291 compounds from 17 different groups ( A~Q ) of their cytotoxicity (assessed by CC 50 ) against four human OSCC (Ca9-22, HSC-2, HSC-3, and HSC-4) and three human normal mesenchymal cells (HGF, HPLF, and HPC), and then their tumor specificity (assessed by TS M , calculated as describe in Figure 2 , and potency-selectivity expression (PSE)) [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. PSE, that reflects both tumor specificity and cytotoxicity against tumor cells, was calculated by dividing the TS M by CC 50 for tumor cells, and then multiplying by 100.…”
Section: Development Of Newly Synthesized Chromone Derivatives Witmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated a total 291 compounds from 17 different groups ( A~Q ) of their cytotoxicity (assessed by CC 50 ) against four human OSCC (Ca9-22, HSC-2, HSC-3, and HSC-4) and three human normal mesenchymal cells (HGF, HPLF, and HPC), and then their tumor specificity (assessed by TS M , calculated as describe in Figure 2 , and potency-selectivity expression (PSE)) [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. PSE, that reflects both tumor specificity and cytotoxicity against tumor cells, was calculated by dividing the TS M by CC 50 for tumor cells, and then multiplying by 100.…”
Section: Development Of Newly Synthesized Chromone Derivatives Witmentioning
confidence: 99%
“…This demonstrated that only limited numbers of compounds show higher tumor specificity, although their structures are very similar with each other. It is possible that such highly tumor-specific compounds show the optimal 3D structure, since the tumor specificity of chromone compounds shows the tight correlation with chemical descriptors that reflect the 3-D structure ( Table 4 ) [ 33 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Development Of Newly Synthesized Chromone Derivatives Witmentioning
confidence: 99%
“…Chromone (4 H -1-benzopyran-4-one) is a backbone structure of flavonols, flavones, flavanones and isoflavones [29] (Figure 1B). We synthesized eight classes of chromones derivatives (total 134 compounds): 3-styrylchromones (15 compounds) [30,31] (containing compound A), 3-benzylidenechromanones (17 compounds) [32] (containing compound B), 3-styryl-2 H -chromenes (16 compounds) [33] (containing compound C), 2-azolylchromones (24 compounds) [34] (containing compound D), 3-( N -cyclicamino)chromones (15 compounds) [35] (containing compound E), 2-( N -cyclicamino)chromones (15 compounds) [36] (containing compound F), furo[2,3- b ]chromones (12 compounds) [37] (containing compound G) and pyrano[4,3- b ]chromones (20 compounds) [38] (containing compound H). The eight compounds that produced the highest TS value in each group are listed in Figure 4.…”
Section: Chromone Derivatives As New Type Of Anticancer Candidatementioning
confidence: 99%
“…2, Table 1). We reported that 3-styrylchromones [30] and azolylchromones [34] induced apoptosis (caspase-3 activation) in human OSCC cell line. On the contrary, 7-methoxy-2-(4-morpholinyl)-4 H -1-benzopyran-4-one, the most active compound among fifteen 2-( N -cyclicamino)chromone derivatives (structure depicted in Figure 4F) showed an excellent tumor-specificity (TS = 63.4) (Figure 5A), low keratinocyte toxicity (Table 1, Exp.…”
Section: Chromone Derivatives As New Type Of Anticancer Candidatementioning
confidence: 99%
See 1 more Smart Citation